Ethnographic borders and boundaries permeability, plasticity, and possibilities - Rinehart, Robert E. 1951-; Kidd, Jacquie; Barbour, Karen Nicole (Peter Lang, 2021)
"'A stunning collection of border-crossing, transgressive essays on the complexities of living in the twilight zones of the postmodern, complexities made visible by contemporary ethnography at the crossroads. A must read.'- Norman K. Denzin, Emeritus Professor, University of Illinois Immigrants, migrants, displaced and diasporic persons: all have been constrained or enabled by borders of some sort. This bookexplores international cases of how and why such boundaries come to be; who is affected by sociallyconstructed borders; what it means to individuals and nation-states to recognise and deal with arbitrary divisions; and finally, what might be done to find - and act on -solutions to the inequity wrought by these borders and boundaries"--
Keywords: Grenzüberschreitung; Feldforschung; Grenze; Ethnology / Philosophical aspects; Boundaries; Aufsatzsammlung